Analisis Faktor-Faktor yang Mempengaruhi Dividend Payout Ratio dengan Ukuran Perusahaan sebagai Pemoderasi - Irmansyah, Deddy; Nariman, Augustpaosa (Jurnal Paradigma Akuntansi, 2024)
This study aims to determine the effect of liquidity, solvency, profitability, and profit growth on the dividend payout ratio with firm size as a moderating variable. This study uses a sample of 43 manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2017-2019 period. The data processing software used is Eviews version 12 with purposive sampling method. This study uses panel data regression with a fixed effect model. The results of this study indicate that liquidity and profitability have a positive and significant effect on the dividend payout ratio, solvency has a negative and insignificant effect on the dividend payout ratio, and profit growth has a positive and insignificant effect on the dividend payout ratio. Meanwhile, firm size was found to be unable to moderate the relationship between liquidity, solvency, profitability, and profit growth on the dividend payout ratio.